Oncological Outcomes and Hospital Costs of the Treatment in Patients With Rectal Cancer: Watch-and-Wait Policy and Standard Surgical Treatment. Issue 5 (May 2020) - Hupkens, Britt J.P.; Breukink, Stéphanie O.; Stoot, Jan H.M.B.; Toebes, Renee E; van der Sande, Marit E.; Melenhorst, Jarno; Beets, Geerard L.; Dirksen, Carmen D.
Abstract : BACKGROUND: Little is known about the costs of the current treatment strategy in locally advanced rectal cancer, in which patients with a clinical complete response after chemoradiotherapy are treated in a watch-and-wait policy. OBJECTIVE: The aim of this study is to present the oncological outcome and hospital costs of patients with a complete response after chemoradiotherapy (watch-and-wait policy) and patients with an incomplete response after chemoradiotherapy (total mesorectal excision). DESIGN: This was a cohort study. SETTINGS: This study was conducted at an academic and a nonacademic hospital. PATIENTS: Patients with locally advanced rectal cancer received either a watch-and-wait policy or total mesorectal excision depending on their clinical response to chemoradiotherapy. INTERVENTIONS: Watch-and-wait policy and total mesorectal excision were the treatments applied. MAIN OUTCOME MEASURES: The primary outcomes measured were overall, local recurrence-free, and distant metastasis-free survival and hospital costs over a 2-year follow-up period. RESULTS: A total of 292 patients with locally advanced rectal cancer were included. Mean age was 65.1 years, and 64.7% were men. One hundred five patients were included in the watch-and-wait subgroup, and 187 patients were in the total mesorectal excision subgroup. Both subgroups showed good oncological outcomes. Hospital costs consisted of 5 categories: costs of primary surgery, costs of adjuvant chemotherapy, costs of examinations, costs of additional surgery, and costs of treatment of regrowth/metastasis. The mean costs per patient were [Euro sign]6713 (watch-and-wait subgroup) and [Euro sign]17, 108 (total mesorectal excision subgroup) over the first 2 years. LIMITATIONS: This study was limited by the following: costs were only from a hospital perspective, follow-up was 2 years, the study was retrospective in part, and there was no comparative study. CONCLUSIONS: Overall survival was good in both subgroups and comparable to literature. The mean costs per patient differ between the watch-and-wait subgroup ([Euro sign]6713) and the total mesorectal excision subgroup ([Euro sign]17, 108). No comparison between the groups could be made. Based on the results of this study, the current strategy, where patients with a clinical complete response are treated in a watch-and-wait policy, and patients with an incomplete response are treated with total mesorectal excision, is likely to be (cost)saving. See Video Abstract at http://links.lww.com/DCR/B177 . RESULTADOS ONCOLÓGICOS Y COSTOS HOSPITALARIOS EN EL TRATAMIENTO DE PACIENTES CON CANCER DE RECTO: ACTITUD DE ESPERA-VIGILANCIA Y TRATAMIENTO QUIRÚRGICO ESTANDARD: ANTECEDENTES: Se sabe poco sobre el costo del tratamiento actual en casos de cancer de recto localmente avanzado, cuando se aplica una política de vigilancia y espera en aquellos pacientes que presentan una respuesta clínica completa después de radio-quimioterapia. OBJETIVO: El propósito final del presente estudio es dar a conocer el resultado oncológico y los costos hospitalarios de los pacientes que presentan una respuesta clínica completa después de radio-quimioterapia (actitud de vigilancia-espera) y los pacientes con una respuesta incompleta después luego de radio-quimioterapia (excisión total del mesorrecto-ETM). DISEÑO: Estudio de cohortes. LUGARES: Hospitales académicos y no académicos. PACIENTES: Todos aquellos pacientes tratados por un cáncer de recto localmente avanzado y que fueron seguidos con una política de vigilancia y espera o la ETM, en función de la respuesta clínica a la radio-quimioterapia. INTERVENCIONES: Políticas de vigilancia-espera, excisión total del mesorrecto. PRINCIPALES RESULTADOS: Sobrevida global libre de recurrencia local, metástasis a distancia, sobrevida libre de enfermedad y costos hospitalarios durante un período de seguimiento de dos años. RESULTADOS: Se incluyeron 292 pacientes diagnosticados de cancer de recto localmente avanzado. La edad media fue de 65, 1 años, 64, 7% eran de sexo masculino. Se incluyeron 105 pacientes en el subgrupo de vigilancia-espera, y 187 en el subgrupo de excisión total del mesorrecto. Ambos subgrupos mostraron optimos resultados oncológicos. Los costos hospitalarios se dividieron en cinco categorías: costos de cirugía primaria; costos de quimioterapia adyuvante; costos de exámenes; costos de cirugía adicional; y costos del tratamiento de rebrote / metástasis. Los costos medios por paciente fueron de [Euro sign] 6.713 (subgrupo de espera-vigilancia) y [Euro sign] 17.108 (subgrupo de excisión total del mesorrecto) durante los primeros dos años. LIMITACIONES: Analisis de costos desde una perspectiva hospitalaria durante un seguimiento de dos años, estudio parcialmente retrospectivo, no comparativo. CONCLUSIONES: La sobrevida general fue optima en ambos subgrupos y comparable con la literatura. El costo promedio por paciente difiere entre el subgrupo de vigilancia y espera ([Euro sign] 6.713) con el subgrupo de la ETM([Euro sign] 17.108). No se pudieron comparar definitivamente ambos grupos. Basados en los resultados del presente estudio, es probable que la estrategia actual, en la que los pacientes con respuesta clínica completa sean tratados con una política de vigilancia y espera, presenten muy probablemente un cierto ahorro en el costo con relación a los pacientes con una respuesta incompleta tratados con excisión total del mesorrecto. Consulte Video Resumen en http://links.lww.com/DCR/B177 . (Traducción—Dr. Xavier Delgadillo )